ANALISIS PROSEDUR KLAIM BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KESEHATAN DI RUMAH SAKIT BHAKTI ASIH BREBES - Iskandar Iskandar (Jurnal Strategik, 2016)
ABSTRACT National health insurance has already implemented by Bhakti Asih (BA) Hospital since January, 1st 2014. Ever since it has been implemented, they had some problems such as claim denied. In 2015 there were 144 cases of claim denied in outpatient service and it increased in 2016 with 185 cases. One of claim denied cause is validity claim document. This research is a qualitative research with case study from three of claim denied documents. This research uses some collection methods such as in-depth interviews, observation and document study. The informants for this research are person in charge of outpatient registration, outpatient registration officer, person in charge of SEP maker, SEP maker, recapitulation officer, person in charge and claim administration officer. The result shows that from validity part of three claim domcuments denied there are still validity. However, from completeness and filling time part there are no any problems found. But there are some problems that cause claim documents denied such as the amount of visiting is more than four times a month and patients that refuse the treatment from their doctor. Based on the system approach, administration services for JKN patient registration, service for making SEP, and recapitulation have not run optimally. It is recommended that the hospital conduct additional claims submission officers, training claim officers, making SOPs about the suitability of filing JKN claims, and adding the number of computer equipment. Keywords: JKN, Claim Denied, Claim File, Hospital, BPJS health.